2019
DOI: 10.3390/cancers11070982
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Enhances Oxaliplatin-Induced Autophagic Cell Death via the ER Stress/Sesn2 Pathway in Colorectal Cancer

Abstract: Oxaliplatin is an anticancer drug administered to colorectal cancer (CRC) patients in combination with 5-fluorouracil and antibodies (bevacizumab and cetuximab), thereby significantly improving the survival rate of CRC. However, due to various side effects associated with the above treatment strategy, the need for combinatorial therapeutic strategies has emerged. Based on the demand for new combinatorial therapies and the known antitumor effects of the omega-3 polyunsaturated fatty acid, docosahexaenoic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 41 publications
5
24
1
Order By: Relevance
“…The upregulation of INHBE is also a marker of the ER-stress induction in DHA-treated cells and may act on cell growth inhibition [77]. The triggering of ER-stress-induced apoptosis by DHA agrees with previous studies using colon, colorectal, and glioma cancer cells [54,[78][79][80] and even in non-alcoholic steatohepatitis patients [81]. In addition, the Glutathione-Specific Gamma-Glutamyl-cyclo-transferase encoded by the CHAC1 gene, which is also upregulated, induces a glutathione depletion that is an important factor for apoptosis initiation and execution, and thus, acts as a pro-apoptotic component of the unfolded protein response pathway by mediating the pro-apoptotic effects of the ATF4-DDIT3/CHOP cascade [82].…”
Section: Antiproliferative Effect and Induction Of Apoptosissupporting
confidence: 82%
“…The upregulation of INHBE is also a marker of the ER-stress induction in DHA-treated cells and may act on cell growth inhibition [77]. The triggering of ER-stress-induced apoptosis by DHA agrees with previous studies using colon, colorectal, and glioma cancer cells [54,[78][79][80] and even in non-alcoholic steatohepatitis patients [81]. In addition, the Glutathione-Specific Gamma-Glutamyl-cyclo-transferase encoded by the CHAC1 gene, which is also upregulated, induces a glutathione depletion that is an important factor for apoptosis initiation and execution, and thus, acts as a pro-apoptotic component of the unfolded protein response pathway by mediating the pro-apoptotic effects of the ATF4-DDIT3/CHOP cascade [82].…”
Section: Antiproliferative Effect and Induction Of Apoptosissupporting
confidence: 82%
“…ER stress is activated by a variety of factors and triggers the unfolded protein response (UPR), which restores homeostasis or activates cell death (34). Previous studies have reported that UPR signaling pathways are closely related to autophagy, apoptosis, inflammatory response and oxidative stress in cancer cells (35)(36)(37). The PERK/ATF4/CHOP pathway plays an important role in modulating anti-and pro-apoptotic proteins, such as B-cell lymphoma-2 (Bcl-2) family members that control mitochondrial apoptosis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagic cell death is one of the major mechanisms that induced programmed cell death. It was found that autophagic cell death played an important role in anticancer drugs [20,21]. DHA could induce autophagy in some human cancer cell lines, including esophageal cancer cells [22][23][24], while the precise mechanisms of DHA on cancer cells were still limited.…”
mentioning
confidence: 99%